INTEGRASI PENDIDIKAN KARAKTER ISLAM DALAM MEWUJUDKAN SEKOLAH RAMAH SANTRI DI MA PROGRESIF UMMUL QURO KABUPATEN PROBOLINGGO - Jamal Malik; Khoiriyah (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study aims to explore the implementation of Islamic character education at MA Progresif Ummul Quro, Bantaran, Probolinggo, and its impact on student behavior and morality. Islamic character education at MA Progresif Ummul Quro is integrated into the curriculum and extracurricular activities to develop students who are not only academically intelligent but also possess noble morals. The research findings indicate that most students feel the Islamic character education received at school has a positive impact on their behavior, both inside and outside of school. However, this study also uncovered several challenges, such as time constraints within the curriculum, a lack of structured materials, and limited support from parents and the community. This research makes an important contribution to the development of Islamic character education theory in Madrasah Aliyah (Islamic Senior High School) and provides new insights into the integration of Islamic character education into students' daily lives. Overall, MA Progresif Ummul Quro has the potential to serve as a model for other schools in creating an environment that supports the development of comprehensive Islamic character. This study recommends better structuring Islamic character education materials, allocating more time, and increasing parental and community involvement to support the teaching of Islamic character in schools.